Aquaculture expansion in Brazilian freshwaters against the Aichi Biodiversity Targets - Junior, Dilermando Pereira Lima; Magalhães, André Lincoln Barroso; Pelicice, Fernando Mayer; Vitule, Jean Ricardo Simões; Azevedo-Santos, Valter M.; Orsi, Mário Luís; Simberloff, Daniel; Agostinho, Angelo Antônio (Ambio, 2018)
The Convention on Biological Diversity proposed the Aichi Biodiversity Targets to improve conservation policies and to balance economic development, social welfare, and the maintenance of biodiversity/ecosystem services. Brazil is a signatory of the Aichi Biodiversity Targets and is the most diverse country in terms of freshwater fish, but its national policies have supported the development of unsustainable commercial and ornamental aquaculture, which has led to serious disturbances to inland ecosystems and natural resources. We analyzed the development of Brazilian aquaculture to show how current aquaculture expansion conflicts with all 20 Aichi Targets. This case suggests that Brazil and many other megadiverse developing countries will not meet international conservation targets, stressing the need for new strategies, such as the environmental management system, to improve biodiversity conservation.